Designing payments for environmental services in theory and practice: an overview of the issues - Engel, S.; Pagiola, S.; Wunder, Sven (Elsevier, 2008)
Payments for environmental services (PES) have attracted increasing interest as amechanism to translate external, non-market values of the environment into real financial incentives for local actors to provide environmental services (ES). In this introductory paper, we set the stage for the rest of this Special Issue of Ecological Economics by reviewing the main issues arising in PES design and implementation and discussing these in the light of environmental economics. We start with a discussion of PES definition and scope. We proceed to review some of the principal dimensions and design characteristics of PES programs and then analyze how PES compares to alternative policy instruments. Finally, we examine in detail two important aspects of PES programs: their effectiveness and their distributional implications. PES is not a silver bullet that can be used to address any environmental problem, but a tool tailored to address a specific set of problems: those in which ecosystems are is managedbecause many of their benefits are externalities from the perspective of ecosystem managers. PES is based on the beneficiary-pays rather than the polluter-pays principle, and as such is attractive in settings where ES providers are poor, marginalized landholders or powerful groups of actors. An important distinction within PES is between user-financed PES in which the buyers are the users of the ES, and government-financed PES in which the buyers are others (typically the government) acting on behalf of ES users. In practice, PES programs differ in the type and scale of ES demand, the payment source, the type of activity paid for, the performance measure used, as well as the payment mode and amount. The effectiveness and efficiency of PES depends crucially on program design.